Higher risk of mood disorders among adolescents with ADHD and asthma: A nationwide prospective study - Chen, Mu-Hong; Su, Tung-Ping; Chen, Ying-Sheue; Hsu, Ju-Wei; Huang, Kai-Lin; Chang, Wen-Han; Chen, Tzeng-Ji; Bai, Ya-Mei (Journal of affective disorders, 2014)
Attention-deficit hyperactivity disorder (ADHD) and asthma are commonly comorbid together, and are associated with an increased risk of development of mood disorders separately. However, there has been no study investigating the comorbid effect of these two disorders on developing mood disorder. Using the National Health Insurance Research Database, adolescents with ADHD-alone, asthma-alone, ADHD comorbid with asthma, and age-/gender-matched (1:4) controls were recruited in 2003. Subjects who developed major depression, any depressive disorder, or bipolar disorder during the follow-up period (2003–2010) were identified. In all, 1172 adolescents with ADHD-alone, 487 with asthma-alone, 238 with ADHD+asthma, and 7552 controls were recruited in 2003. Adolescents with ADHD+asthma and those with ADHD-alone, but not those with asthma-alone, had an elevated risk of developing major depression (hazard ratio [HR]: 10.25, 95% confidence interval [CI]: 3.86–27.19; HR: 8.64, 95%CI: 5.00–14.93; HR: 2.11, 95%CI: 0.71–6.23) and bipolar disorder (HR: 31.25, 95%CI: 8.87–110.12; HR: 10.42, 95%CI: 4.60–23.63; HR: 1.91, 95%CI: 0.24–15.32) compared to the control group. Our results showed that ADHD adolescents had an increased risk of developing both unipolar depression and bipolar depression in their later life, and that the comorbidity of asthma with a synergistic effect increased this risk further. The underlying pathophysiology among ADHD, asthma, and mood disorders needs further investigation.